2021
DOI: 10.1523/eneuro.0077-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Severe Sleep Disruption on the Synaptic Ultrastructure of Young Mice

Abstract: There is molecular, electrophysiological and ultrastructural evidence that a net increase in synaptic strength occurs in many brain circuits during spontaneous wake or short sleep deprivation, reflecting ongoing learning. Sleep leads instead to a broad but selective weakening of many forebrain synapses, thus preventing synaptic saturation and decreasing the energy cost of synaptic activity. Whether synaptic potentiation can persist or further increase after long sleep deprivation is unknown. Whether synaptic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…Through SBF-SEM another parameter was established, the axon spine interface (ASI), defined as the interfacing surface between the presynaptic bouton and the spine head (Bellesi et al, 2015) and it represents the 3D equivalent of the length of the synaptic cleft which can be observed and accurately measured in TEM images (Colombo et al, 2021). The ASI and the PSD size were shown to be strongly correlated as they both become larger upon synaptic potentiation (Cheetham et al, 2014;De Vivo et al, 2017) and both correlated with the amplitude of excitatory postsynaptic currents (Murru et al, 2017;Nagai et al, 2021). Indeed, the tight relationship between the surface area of the ASI and the functional state of the synapse was demonstrated in a number of studies exploring the effects of sleep and sleep deprivation in homeostatic scaling of neural circuits.…”
Section: Postsynaptic Density Synaptic Apposition Surface (Sas) and A...mentioning
confidence: 97%
See 1 more Smart Citation
“…Through SBF-SEM another parameter was established, the axon spine interface (ASI), defined as the interfacing surface between the presynaptic bouton and the spine head (Bellesi et al, 2015) and it represents the 3D equivalent of the length of the synaptic cleft which can be observed and accurately measured in TEM images (Colombo et al, 2021). The ASI and the PSD size were shown to be strongly correlated as they both become larger upon synaptic potentiation (Cheetham et al, 2014;De Vivo et al, 2017) and both correlated with the amplitude of excitatory postsynaptic currents (Murru et al, 2017;Nagai et al, 2021). Indeed, the tight relationship between the surface area of the ASI and the functional state of the synapse was demonstrated in a number of studies exploring the effects of sleep and sleep deprivation in homeostatic scaling of neural circuits.…”
Section: Postsynaptic Density Synaptic Apposition Surface (Sas) and A...mentioning
confidence: 97%
“…These studies showed that synaptic potentiation was associated with enlargement of the ASI in a subset of synapses when the animals were exposed to learning tasks during the wake period, while it underwent renormalization during sleep, possibly to consolidate and integrate memories and to avoid circuit saturation (Cirelli and Tononi, 2020). In fact, it has been shown that sleep induced reduction of the ASI both in hippocampal CA1 and primary motor cortex neurons (De Vivo et al, 2017); accordingly, chronic sleep deprivation led to ASI expansion in hippocampal CA1 (Spano et al, 2019;Nagai et al, 2021). Together with a reduction of the ASI, AMPA glutamate receptor (AMPAR) expression at the postsynaptic membrane was reduced after sleep (De Vivo et al, 2017;Miyamoto et al, 2021); and, in line with these findings, the levels of AMPAR and its phosphorylation were shown to diminish during sleep through a mechanism dependent on the increased synaptic concentration of Homer1a (Diering et al, 2017).…”
Section: Postsynaptic Density Synaptic Apposition Surface (Sas) and A...mentioning
confidence: 99%
“…Changes in spine density are the most overlapping finding in developmental sleep disruption paradigms. Normal sleep functions to modulate spine density as evidenced by acute disruption paradigms and alterations have been seen in post-mortem tissue of individuals with ASD ( Nagai et al, 2021 ; de Vivo and Bellesi, 2019 ; de Vivo et al, 2016 ; Bellesi et al, 2015 ; Hutsler and Zhang, 2010 ). It is plausible that prolonged disrupted sleep in development can modify and have persistent effects on cellular composition.…”
Section: Neural Consequences Of Developmental Sleep Disruptionmentioning
confidence: 99%
“…Cage manipulation includes cage-shaking using an orbital shaker ( Jones et al, 2019a ; Lord et al, 2022 ) or insertion of novel objects to force locomotion ( Li et al, 2017 ). Cage manipulation presents the opportunity for potential automated disruption that is either continuous, targeting only the light-phase (when rodents are most likely to be asleep), and/or using closed loop delivery of disruption based on EEG/EMG activity ( Jones et al, 2019a , 2019b , 2020 , 2021 ; Lord et al, 2022 ; Bian et al, 2022 ; Feng et al, 2000 ; Nagai et al, 2021 ). An animal's cage includes its light source, the developmental chronic circadian disruption (DCCD) paradigm mimics severe shift-work with the light cycle advances dramatically every other or every fourth day ( Smarr et al, 2017 ; Ameen et al, 2022 ).…”
Section: Introduction: Function Of Normal Sleep In Developmentmentioning
confidence: 99%
“…The authors suggested that a single episode of sleep deprivation has no major neuroanatomical changes. On the other hand, given the previous studies demonstrating that sleep does regulate the dynamics and ultrastructure of cortical and hippocampal spines in juvenile mice (Maret et al, 2011;Yang et al, 2014;de Vivo et al, 2017;Li et al, 2017;Spano et al, 2019;Zhou et al, 2020;Nagai et al, 2021), it is also likely that the impact of sleep deprivation on dendritic spines is more profound during development than in adulthood.…”
Section: Editorial On the Research Topic Sleep Deprivation Circadian ...mentioning
confidence: 99%